Legal Analysis Related to Emergency Defense Against the Threat of Criminal Acts of Begal (Case Study of Surakarta District Court) - Idham Mufi Baihaqi; Natangsa Surbakti (Proceeding International Conference Restructuring and Transforming Law, 2023)
Begal is a serious crime. Today, we encounter this type of crime in several cases and some criminal news. A lot of polemic arose when a case of self‐defense from a victim of robbery ended in conviction for murder, although in the end he was acquitted. Self‐forced defense is regulated in Article 49 of the Criminal Code which states that a person who defends by force cannot be convicted, in other words when someone is threatened or threatened with his life he will be killed by being mugged even if the defense that occurs in it is not a crime. This research uses a sociological juridical analysis technique, so this research will focus on jurisprudence and legal material in it can be in the form of court decisions and laws which will then be reflected in their application to the wider community. Because in this case, the victims of robbery who defended what happened to him had to serve prison sentences with the offense of murder.